Perlindungan Hukum Hak Cipta Atas Karya Motif Batik Galuh Di Kabupaten Gianyar - AA Mas Pradnyandari Mantara; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Jurnal Interpretasi Hukum, 2021)
Legal protection for intellectual works is not only shown to works whose copyright has been registered, but also to those whose copyrights have not been or are not registered at all. The purpose of this study is to determine the legal protection of Galuh batik motifs in Gianyar Regency according to Law Number 28 of 2014 concerning copyright and to find out the copyright registration for Galuh batik business in Gianyar Regency. The author uses the type of empirical legal research, namely research by means of interviews which primary data are known as field research. The data needed in this study are primary and secondary data. Based on the results of the study, it can be concluded that the legal protection of Galuh batik motifs in Gianyar Regency based on Law Number 28 of 2014 concerning copyright, namely Galuh Batik has not received optimal legal protection. If in the future there is a dispute, then the Batik Galuh Party can take it with a Civil Dispute settlement. The registration process for Batik Galuh copyright still uses a manual system and the process is completed in less than 3 weeks to 1 month.